Integrating Mental And Psychosocial Readiness Into Military Human Resource Policy For Conflict Zone Deployment In Indonesia - Chandra Kusumawardhani; Guntur Eko Saputro; Sutanto (UNIVERSITAS PAKUAN, 2026)
This study examines the strategic role of mental and psychosocial readiness as an integral component of military human resource management within conflict environments, with a particular focus on its legal and policy implications for the Indonesian National Armed Forces (TNI). Employing a Systematic Literature Review (SLR) of 30 peer-reviewed and institutional sources published between 2019 and 2025, this study synthesizes empirical evidence and normative frameworks across five core domains: mental readiness, psychosocial support systems, deployment stress in conflict zones, post-traumatic stress disorder (PTSD) risk, and military mental health governance. The findings demonstrate that soldiers with higher levels of mental preparedness and structured psychosocial support exhibit superior operational performance, ethical decision-making, adaptability, and emotional stability under prolonged stress exposure. Conversely, inadequate mental and psychosocial readiness significantly increases vulnerability to psychological distress, PTSD, operational errors, and long-term institutional burden. From a policy perspective, the study identifies a critical gap between scientific evidence and the existing regulatory framework governing military human resource management in Indonesia, where mental readiness has not yet been explicitly institutionalized as a formal indicator of operational readiness.This article argues that mental and psychosocial readiness must be repositioned from an individual health concern to a legally component of defense governance. Keywords : Conflict Zone, Defense Policy, Mental Readiness, Psychosocial